1989
DOI: 10.3109/09687688909026815
|View full text |Cite
|
Sign up to set email alerts
|

Putative Cocaine Receptor in Striatum Is a Glycoprotein with Active Thiol Function

Abstract: Dopamine transporters of bovine and rat striata were identified by their specific [3H]cocaine binding and cocaine-sensitive [3H]dopamine [( 3H]DA) uptake. Both binding and uptake functions of bovine striatal transporters were potentiated by lectins. Concanavalin A (Con A) increased the velocity but did not change the affinity of the transporter for DA; however, it increased its affinity for cocaine without changing the number of binding sites. This suggests that the DA transporter is a glycoprotein and that Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…If occupancy of only one cocaine site is sufficient to block dopamine uptake through the dimer, it would explain the general assumption that inhibition of dopamine uptake by blockers requires no more than one molecule to block transport of one molecule of dopamine, in agreement with the monophasic nature of the inhibition curves observed for most compounds (Richelson and Pfenning 1984;Andersen 1987;Cao et al 1989;Krueger 1990;Reith et al 1996a;Eshleman et al 1999). Thus, for each translocation cycle, dopamine needs to use only one of the two available dopamine recognition sites per dimer, and cocaine will competitively inhibit regardless of which site dopamine used.…”
Section: Dat Oligomers?mentioning
confidence: 62%
See 1 more Smart Citation
“…If occupancy of only one cocaine site is sufficient to block dopamine uptake through the dimer, it would explain the general assumption that inhibition of dopamine uptake by blockers requires no more than one molecule to block transport of one molecule of dopamine, in agreement with the monophasic nature of the inhibition curves observed for most compounds (Richelson and Pfenning 1984;Andersen 1987;Cao et al 1989;Krueger 1990;Reith et al 1996a;Eshleman et al 1999). Thus, for each translocation cycle, dopamine needs to use only one of the two available dopamine recognition sites per dimer, and cocaine will competitively inhibit regardless of which site dopamine used.…”
Section: Dat Oligomers?mentioning
confidence: 62%
“…Although inhibition of dopamine uptake by cocaine via the neuronal dopamine transporter in the striatum and nucleus accumbens has been reported to be of a non-or uncompetitive type (Missale et al 1985;McElvain and Schenk 1992;Wheeler et al 1994;Povlock and Schenk 1997), most studies indicate a competitive mechanism (Richelson and Pfenning 1984;Andersen 1989;Cao et al 1989;Krueger 1990;Jones et al 1995;Xu et al 1995;Reith et al 1996a;Garris et al 1998;Wu et al 1998;Eshleman et al 1999). If indeed the mechanism is competitive, there is likely to be a one-to-one relationship between cocaine binding sites and dopamine recognition sites, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies have shown that cocaine inhibits dopamine reuptake through its binding with the extracellularly-open state of DAT 9,10,11,12,27,28,29,32,35,36,38,39. Starting from the newly refined DAT structure bound with dopamine, herein denoted by DAT-DA, molecular docking was carried out by using AutoDock3.0.5 program42 to explore the mode of cocaine binding with DAT in the presence of dopamine.…”
Section: Methodsmentioning
confidence: 99%
“…Posttranslational modifications to the protein itself have been shown to differ between different anatomical areas, predominately in glycosylation (Vaughan et al, 1996), and Cao et al (1989) have shown that cocaine binding is sensitive to changes in external glycosylation. Thus, glycosylation and other posttranslational modifications may differ in expressions systems relative to native systems and result in different behaviors of DAT.…”
Section: Comments On Using Expression Systems To Study the Transportementioning
confidence: 99%